A cost-effective evaluation of biomass district heating in rural communities. (15th January 2016) - Hendricks, Aaron M.; Wagner, John E.; Volk, Timothy A.; Newman, David H.; Brown, Tristan R.
Highlights: Develop a cost-effective model using secondary data examining delivering heat through Biomass District Heating (BDH). Eight of ten rural villages studied could cost-effectively deliver heat through BDH below the 2013 price of heating oil. 80% of the annual cost of BDH was attributable to capital expenses. Erratic fuel oil prices substantially impact future feasibility. Village level feasibility is highly-influenced by the presence of large heat demanders. Abstract: The economic feasibility of Biomass District Heating (BDH) networks in rural villages is largely unknown. A cost-effective evaluation tool is developed to examine the feasibility of BDH in rural communities using secondary data sources. The approach is unique in that it accounts for all the major capital expenses: energy center, distribution network, and energy transfer stations, as well as biomass procurement. BDH would deliver heat below #2 fuel oil in eight of the ten rural study villages examined, saving nearly 500, 000 per year in heating expenses while demanding less than 5% of the forest residues sustainably available regionally. Capital costs comprised over 80% of total costs, illuminating the importance of reaching a sufficient heat density. Reducing capital costs by 1% lowers total cost by 93, 000 per year. Extending capital payment period length five years or lowering interest rates has the next highest influence decreasing delivered heat price 0.49% and 0.35% for each 1% change, respectively. This highlights that specific building heat is a strong determinant of feasibility given the relative influence of high-demanding users on the overall village heat-density. Finally, we use a stochastic analysis projecting future #2 fuel oil prices, incorporating historical variability, to determine the probability of future BDH feasibility. Although future oil prices drop below the BDH feasibility threshold, the villages retain a 22–53% probability of feasibility after 20 years as a result of high #2 fuel oil price variability.